Reconocemos los cambios de una magnitud con el paso del tiempo - Chuquiviguel Centurion, Jaime (2018)
This sufficiency research has been prepared for third grade students of Elementary Education in Trujillo city in 2019, with the titled topic: "We change over time", in which everyday situations have been taken into account in wich students daily establish equivalence relationships and magnitude changes with respect to the time passage . In preparing the session, we have worked with the pedagogical and didactic processes of the Mathematics area to promote expected and significant learning. This strategies were designed to promote active and meaningful participation all students. It is intended at all times to awaken the interest and motivation to the student for mathematics area, since it is a very important one.